A ênfase na aprendizagem e a educação contemporânea - BASTOS, Rachel Benta Messias (2006)
This study, tied to line of research of Culture and Educational Processes, aims to discuss the learning and some of its appropriations in contemporary education. Understanding learning as a universal category subject to historical particularities, this literature and exploratory study was proposed to seize ownership of education nowadays, by reference (1) the guidelines that govern macropolitical education and (2) Master's dissertations in education (1990 - 2000). The emphasis on learning has been identified in the documents studied, in particular the reports to Learn to be Aprender a ser (1970) and Education: The Treasure Within Educação: um tesouro a descobrir (1990), which were proposed as a new education, geared towards the action of the individual student and individualization of the educational processes , focusing on the subject, and also in the discourse sought to justify the need for change, referring to new paradigms of learning, learning to learn. Learning was cited as an important category in 71.2% of the dissertations studied. These essays showed that learning is a category that articulates the new directions of education conducted in the light of psychological benchmarks, especially Piaget and Vygotsky. The two sources relate the idea of a learning innovation in educational practice. It was concluded that the emphasis on innovations in educational practices under the guidance of a possible "revival of learning" meets new forms of organization of productive forces and social relations produced in this historical particularity. Teaching and learning are split and included in their externality corroborate functional educational concept on effective society. It reaffirms the assumption of a learning rule on education in contemporary education, which is expressed in the critique of traditional education.